Profitabilitas, Likuiditas, Leverage, Corporate Social Responsibility dan Nilai Perusahaan - Wahyuniyasanti, Cokorda Istri; Mertha, Made (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
Firm value is the achievement obtained by the company from public trust after running operations. The purpose of this study is to obtain empirical evidence regarding the effect of profitability, liquidity, leverage, and CSR on firm value. This research was conducted in financial sector companies listed on the Indonesia Stock Exchange. The sample of companies is 10 companies with 5 years of observation, then obtained 50 observational data. The method of determining the sample used in this study is non-probability sampling with purposive sampling technique. The data were collected, then tested with Statistical Product and Service Solutions (SPSS) analysis. The results showed that profitability and leverage had a positive effect on firm value and liquidity and CSR had no effect on firm value. Keywords: Company Value; Profitability; Liquidity; Leverage; Corporate Social Responsibility .